Genotypic variation and talent identification in sports - Pramanik, A.; Das, S.; Dandapat, S. (IntechOpen, 2021)
Top performance of athletes is not limited to the demand of fame, public recognition, sponsorship, and prize money but genetic inheritance contributes a prime role to hold such traits. Recent years, we have witnessed the rise of sports specific tests that identify person`s athletic talents, but human vary on genetic factors which silently work to achieve success in sports. Recent progress on the genetic determination in the sports sciences offer great perspective to analyze the genotype profile associated with the athletes. One of the most used advances in this field is the identification of variations in the DNA sequence, known as Single Nucleotide Polymorphisms (SNPs). Genetic evaluations should be combined with other tools to get an accurate identification of athletes and their respective fields to achieve optimum success.